Exercise sensitizes PD-1/PD-L1 immunotherapy as a hypoxia modulator in the tumor microenvironment of melanoma - Yan, Huiyu; Jiang, Aimin; Huang, Yinong; Zhang, Jun; Yang, Wenguang; Zhang, Wei; Liu, Tianya (Frontiers in Immunology, 2023)
Introduction: Hypoxia is associated with unfavorable prognoses in melanoma patients, and the limited response rates of patients to PD-1/PD-L1 blockade could be attributed to the immunosuppressive tumor microenvironment induced by hypoxia. Exercise offers numerous benefits in the anti-tumor process and has the potential to alleviate hypoxia; however, the precise mechanisms through which it exerts its anti-tumor effects remain unclear, and the presence of synergistic effects with PD-1/PD-L1 immunotherapy is yet to be definitively established.We established a B16F10 homograft malignant melanoma model and implemented two distinct exercise treatments (low/moderate-intensity swim) based on the mice's exercise status. The specific function manner of exercise-induced anti-tumor effects was determined through RNA sequencing and analysis of changes in the tumor microenvironment. Furthermore, moderate-intensity swim that exhibited superior tumor suppression effects was combined with Anti-PD-1 treatment to evaluate its in vivo efficacy in mouse models.Results: Exercise intervention yielded a considerable effect in impeding tumor growth and promoting apoptosis. Immunohistochemistry and RNA sequencing revealed improvements in tumor hypoxia and down-regulation of hypoxia-related pathways. Cellular immunofluorescence and ELISA analyses demonstrated a notable increase of cytotoxic T cell amount and a decrease of regulatory T cells, indicating an improvement of tumor immune microenvironment. In comparison to Anti-PD-1 monotherapy, tumor suppressive efficacy of exercise combination therapy was found to be enhanced with improvements in both the hypoxic tumor microenvironment and T cell infiltration.Exercise has the potential to function as a hypoxia modulator improving the tumor immune microenvironment, resulting in the promotion of anti-tumor efficacy and the facilitation of biologically safe sensitization of PD-1/PD-L1 immunotherapy.